THE SHELF-LIFE PREDICTION OF SWEET SOY SAUCE USING ASLT METHOD WITH ARRHENIUS MODEL - Yuwono, Sudarminto Setyo; Liyundzira, Fasandra Novi; Wulandari, Eka Shinta (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
Sweet soy sauce is a typical Indonesian soy sauce. One of soy sauce producers in Malang Regency is Jawa Sehati Mulia SMEs. This SMEs has not yet estimated the shelf life of sweet soy sauce product so that the current shelf life refers to other commercial products. The purposes of this study were to determine the characteristics quality and to estimate the shelf life of Tugu Jawa sweet soy sauce. The product was stored at 31, 34, and 37 °C and the organoleptic, microbiological, physical, and chemical characteristics were analysed every seven days. The result showed that the critical parameter was pH because it has the lowest activation energy value. Changes in pH parameter values follow first order with a linear regression equation y = -4.115,68x + 7,33 so that the estimated shelf life of sweet soy sauce was 127,92 days or 4,26 months at room temperature (25 °C).